Daily spectral ocean surface albedo due to small chlorophyll concentrations and cloudy conditions for 440 nm wavelength in coastal waters - Golovchenko, Philipp; Yusri Yusup; Liew, Juneng (Universiti Kebangsaan Malaysia, 2023)
The spectral daily Ocean Surface Albedo (OSA) is a sensitive parameter dependent on sea surface bio-optical properties and solar radiation distribution due to the transmissivity of the atmosphere. We analyzed the OSA sensitivity to the small concentrations of sea surface phytoplankton due to cloudy conditions, based on measured half-hourly global radiation data, and phytoplankton variability represented by chlorophyll-a concentrations at the upper layers over the Malacca Strait. The influence of the sea surface phytoplankton was examined by using the chlorophyll-a maximum absorption wavelength (440 nm) for a detailed examination of the real phytoplankton impact presented by small concentrations (0.39 - 0.69 mg/m3). The atmosphere transmittance determination was made over the period from January 2016 to March 2016 and January 2017 to March 2017 using hourly clearness index (KTh) estimation. The aim of current study was to examine the influence of sea surface phytoplankton concentrations on the radiation budget and to account the role that the phytoplankton plays in detail short-scale OSA parameterization. Daily timescale spectral OSA includes the bio-optical modelling part, which allowed us to investigate the patterns of diurnal variability of the main reflectance parameters, using Jin et al. scheme for albedo components (direct and diffuse) estimation, was computed. The OSA variability analysis confirmed the bio-optical feedback presented by apparent properties of the coastal waters for the observed conditions. The proposed calculation scheme accounted for the sea surface optical behavior with low concentrations of chlorophyll-a and suggests that albedo variability depends not only on the angle factors, even with the low phytoplankton influence (less than 1 mg/m3). It was found that the phytoplankton pigment absorption properties have less effect in albedo parameterization while the chlorophyll-a concentrations are less than 0.5 mg/m3.